Grails Persistence with GORM and GSQL - Fischer, Robert (Apress, 2012)
When you stop for a moment to consider what we are doing, it is really astounding. We are trying to comprehend some kind of process or system with all of its emergent and dynamic aspects, with its historical artifacts and experimental features, and to somehow encode that comprehension onto an electrically-charged platter. Most of the time, we’re not just adjusting the electrical charge on the platter in front of us, though—that’d be too easy. We want to encode the information of this system into some electrically-charged platter that we have never even seen, and have only experienced by way of many, many levels of intermediaries. In short, we are communicating the behavior of an entire system to an electrically charged platter far away via an astoundingly automated game of telephone. ¬«